The Types of Discrimination and Princess Diana’s Ways to Pursue Her Freedom in Spencer (2021) - Salma, Nabila; Nirwan, Nirwan; Ramadhina, Retno (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This article elaborates the film "Spencer," characterized as "a fable from true tragedy" based on Princess Diana's story. The focus of the research is on how Princess Diana pursued her freedom. The methodology involves a direct viewing and interpretation of "Spencer," analyzing visual scenes and audio dialogues. Following Roland Barthes' semiotic approach, the researcher identifies denotative signs, transitions them into connotative markers, and ultimately explores the mythic stage. Specific scenes, such as Princess Diana encountering a sign urging silence and her secretive actions in the palace, are dissected to reveal layers of meaning. Through semiotic analysis, the article illustrates Princess Diana's attempts to break free from royal constraints. Each scene reflects the conflict between individual desires for freedom and the norms imposed by the royal institution. The study offers a nuanced understanding of Princess Diana's struggle within the royal family's rules and pressures. The analysis provides profound insights into how "Spencer" portrays Princess Diana's quest for personal freedom amidst the rigid regulations of the royal household, employing semiotics as a valuable approach to unravel the meanings embedded in visual and auditory elements of the film.